RMT: A Semi-Automated Tool for Refactoring Design Patterns - Riemer, Yasmin; Nogueira, Pedro Magnus Pedroso; Matos, Simone Nasser; Borges, Helyane Bronoski (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
When done manually, software refactoring becomes a thorough job and can introduce chances of human failure during its application. Automated or semi-automated tools for this purpose can facilitate the refactoring process. This paper presents the semi-automated Refactoring and Measurement Tool (RMT) that performs pattern-based refactoring in source code written in Java. RMT detects and applies design patterns using literature methods and evaluates the benefits of pattern application regarding quality attributes using software metrics. Five tests were performed with Java projects, introducing candidate classes for refactoring the Strategy and Template Method patterns. Link for video: youtu.be/tDWTmFJCfg8 .